Akirin/Subolesin regulatory mechanisms at host/tick–pathogen interactions. Issue 1 (11th November 2021) - de la Fuente, José; Artigas-Jerónimo, Sara; Villar, Margarita
ABSTRACT: Ticks and tick-borne pathogens such as Anaplasma phagocytophilum affect human and animal health worldwide and thus the characterization of host/tick–pathogen interactions is important for the control of tick-borne diseases. The vertebrate regulatory proteins Akirins and its tick ortholog, Subolesin, are conserved throughout the metazoan and involved in the regulation of different biological processes such as immune response to pathogen infection. Akirin/Subolesin have a key role in host/tick–pathogen interactions and exert its regulatory function primarily through interacting proteins such as transcription factors, chromatin remodelers and RNA-associated proteins. Recent results have provided evidence of akirin / subolesin genetic interactions and the interaction of Akirin/Subolesin with histones, thus suggesting a role in direct chromatin remodeling. Finally, and still to be proven, some models suggest the possibility of direct Akirin/Subolesin protein interactions with DNA. Future research should advance the characterization of Akirin/Subolesin interactome and its functional role at the host/tick–pathogen interface. These results have implications for translational biotechnology and medicine for the development of new effective interventions for the control of ticks and tick-borne diseases. Abstract : Akirin/Subolesin regulatory proteins play a key role at the host/tick–pathogen interface in the regulation of different biological processes including immune response to pathogen infection.